Risk Factors For Hypertension In Outpatients at RSUD MGR Gabriel Manek, SVD Atambua: Faktor Risiko Kejadian Hipertensi Pada Penderita Rawat Jalan di RSUD MGR. Gabriel Manek, SVD Atambua - Letto, Laurensiana Christin; Ndoen, Honey Ivon; B. Sir , Amelya; F.E Manurung, Imelda (Universitas Mohammad Husni Thamrin, 2025)
Hypertension or high blood pressure is a risk factor for cardiovascular disease and a cause of premature death in the world. The incidence of hypertension in Belu Regency is quite high in the Regional General Hospital (RSUD) Mgr. Gabriel Manek, SVD Atambua which shows an increase in cases in 2021 from 213 cases increasing to 332 cases in 2022. This study aims to analyze the risk factors associated with the incidence of hypertension in RSUD Mgr. Gabriel Manek, SVD Atambua in 2023. The type of research is analytic epidemiology with a case control design. The case population is all patients suffering from hypertension and the control population is all patients who do not suffer from hypertension who are on outpatient treatment at RSUD Mgr. Gabriel Manek, SVD Atambua. The number of samples with a ratio of 1: 1, namely 67 case samples and 67 control samples, a total of 134 samples. The sampling technique for cases and controls is non-probability sampling, namely accidental sampling. Data collection techniques using interviews and distributing questionnaires. Data analysis technique using Chi-Square statistical test. The results showed that there was an association between age (p value = 0.003, OR = 3.030), family history (p value = <0.001, OR = 12.390), history of alcohol consumption (p value = 0.014, OR = 2.570), and history of sodium consumption (p value = <0.001, OR = 4.543) and there was no association between gender (p value = 0.603) and obesity (p value = 0.724) with the incidence of hypertension at Mgr. Gabriel Manek Hospital, SVD Atambua. Gabriel Manek, SVD Atambua. For the community, it is expected to maintain health by implementing a healthy lifestyle and diet and routinely checking blood pressure in health facilities. Keywords: hypertension, risk factors, outpatients